Strategies to Enhance ZIS Donor Loyalty through Trust Building at Baitul Maal Hidayatullah East Kalimantan - Salamun, Imam (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study is motivated by the limited number of empirical investigations that specifically examine the direct effects of service quality, institutional image, communication, and donation convenience on donor trust, as well as its impact on the loyalty of ZIS (zakat, infaq, and sadaqah) donors. The novelty of this research lies in its focus on a causal relationship model that does not include any mediating variables—distinct from most prior studies which typically position trust merely as an intervening variable.The primary aim of this research is to analyze the extent to which service quality, institutional image, communication, and donation convenience directly influence donor trust, and to assess the direct impact of donor trust on the loyalty of zakat, infaq, and sadaqah donors at the National Amil Zakat Institution (LAZNAS) Baitul Maal Hidayatullah in East Kalimantan.A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Primary data were collected through a structured questionnaire using a 5-point Likert scale, distributed to 240 active donors selected through purposive sampling. Data processing involved several stages, including validity and reliability testing, evaluation of the measurement model, and structural model assessment.The results show that both service quality and institutional image have a positive and significant effect on donor trust. In contrast, communication and donation convenience exhibit a positive but statistically insignificant influence. Furthermore, donor trust is proven to have a direct and significant effect in enhancing sustained donor loyalty in ZIS contributions.